PERFORMANCE OF NIGERIAN NEWSPAPERS IN SELECTED POLITICAL CRISIS SITUATIONS (2015)
The press in a democratic setting sets the agenda for the society through news reports, incisive features, editorials and commentaries. Previous studies on press performance, especially during political crisis situations, concentrated more on the extent of reports of such crises and rarely investigate the factors that influence the reportage. This study, therefore, evaluated the performance of the Nigerian newspapers in their coverage of selected political crisis situations in terms of magnitude and frames with a view to identifying how ownership, editorial policies and other factors influenced such performance. The study was anchored on News Framing theory and it adopted the Propagandist, Commercial laissez-faire and Public service models. The selected political crisis situations covered the period between 2005 and 2011: President Obasanjo‘s alleged third-term agenda; the constitutional crisis arising from President Yar‘Adua‘s absence from office and the violent protests that greeted the 2011 presidential elections in the northern part of Nigeria. Daily Trust, The Punch, The Guardian, Nigerian Tribune and The Sun were purposively selected because of their locations and ownership. Five hundred editions were selected through the systematic random sampling technique while ten editors of the newspapers were purposively selected for in-depth interviews. A nine-item coding sheet and a nine-item in-depth interview guide were the instruments of data collection. Quantitative data were analysed using descriptive statistics, and chi-square at P=0.05 level of significance. Explanation building through thematic approach was used to analyse the qualitative data. Yar‘adua‘s illness featured more in the newspapers with 37.0% reports than the third-term agenda and election protests with 31.0% each.Small-sized reports were more prominent than large-sized. The newspapers were more negative in framing election protests (51.3%) and Yar‘adua‘s illness (45.4%) than the third-term agenda (37.2%). The Daily Trust had more favourable reports on Yar‘adua‘s illness and third-term agenda, while other newspapers had more negative reports on the issues. All the newspapers had more negative reports on the election protests. There was a significant difference in the framing of reports among the newspapers: Nigerian Tribune (x = 70.3), Daily Trust (x = 65.0), The Sun (χ = 64.8), The Guardian (x = 63.8), and The Punch (x = 60.1). There was no significant relationship between the editorial policies and performance of the newspapers. The performance rate across the five newspapers differed: Nigerian Tribune (74.4%), The Guardian (71.1%), The Punch (55%), The Sun (51.8%) and the Daily Trust (37.3%).However, the editors perceived that editorial policies, rather than ownership, covertly guided the newspapers‘ operations during the political crisis situations. Ethnicity or sectional interest, funding, production deadline and access to information were other factors that influenced performance. The performance of the newspapers during the political crisis situations varied slightly in terms of magnitude and report framing due to editorial policies. To enhance performance, newspapers should evolve editorial policies that will guarantee fair and balanced report framing and put the public interest above the primordial, sectional and commercial interests of the owners. Key words: Nigerian newspapers, Political crisis situations, Newspapers performance, Ownership of newspapers, News framing. Word count: 484